Ethno-Psychological Aspects of Education of Transcarpathian Region - Maryana Marusynets’ (Pedagogical Discourse, 2012)
The article examines ethnopsychological aspects of the origin of culture, education, science in Transcarpathian region in different periods of existence; the role of priesthood, political and social leaders in the development and establishment of culture and education of countrymen is outlines.